Structure of ancient glass by 29Si magic angle spinning NMR - Bradford, Henry; Ryder, Amy; Henderson, Julian; Titman, Jeremy J. (Wiley, 2018)
29Si magic angle spinning (MAS) NMR spectroscopy is applied for the first time to the structural analysis of ancient glass samples obtained from archaeological excavations. The results show that it is possible to establish the distribution of Si environments in ancient glass by 29Si MAS NMR, so long as the concentrations of magnetic impurities, such as Mn and Fe oxides, are low. In general good agreement has been obtained with compositions found using electron probe microanalysis. In addition, the 29Si MAS NMR data reveal structural differences between glasses manufactured at separate ancient sites.